An assessment of the role of social capital in collaborative environmental governance in tribal communities: the study of Gumbi and Zondi communities in KwaZulu Natal Province, South Africa - Musavengane, Regis (My University, 2017)
Political transformations in most developing nations have been accompanied by vast land claims by indigenous communities who were forcibly detached from their traditional land during colonisation and apartheid-like dispensations. In the context of sub-Saharan African countries (including South Africa), the need for land reform has been aggravated by the great scarcity of farmland. However, most of the reclaimed land is in areas pursuing conservation activities. Now, caught between owning the land and pursuing conservation as a land use option to improve livelihood; local communities have tended to form partnerships and collaborations with external stakeholders in managing communally owned natural resources. Collaborative management is perceived as a sustainable route in governing common pool natural resources in re-claimed areas. It is in this regard, that this research aims at establishing the role to which social capital can be instrumental in promoting sustainable governance in co-managed community game reserves in Kwa-Zulu Natal. This study follows a case study approach, with Zondi and Gumbi communities in Umvoti and uPhongolo Districts of KwaZulu Natal, South Africa respectively being used to obtain empirical evidence. Two basic criteria were taken into consideration in selecting appropriate case study areas to attain the aim of the study. Firstly, whether the area had successfully claimed the land and secondly, if there were collaborative efforts from different stakeholders in managing available common resources. To ensure equal representation, research participants were drawn from households, community leaders, conservation organisations and policy makers from the government. This study’s methodological positionality is interpretive in nature, and its operational framework base is qualitative research. It therefore uses a number of qualitative techniques in an attempt to establish the role of social capital in governing Somkhanda (in Gumbi) and Ngome (in Zondi) Community Game Reserves. For instance, systemic-resilience thinking and socio-ecological learning approaches were used to analyse the participatory relationship and effects in managing community natural resources in Gumbi and Zondi communities. It has been revealed in this study that the key to successful collaborative environmental management projects revolves around issues of participation, transparency, reciprocity and effective communication. These elements are important ingredients in building strong social capital. Community social cohesion builds trust between internal and external actors, especially in communities that were once subjected to various forms of segregation and corrupt systems of governance. The presence of trust in managing common pool resources ensures effective stakeholder participation as well as involvement in decision making processes. Furthermore, the evidence from this study suggests that the frequent exclusion of rural populations from participation in processes with a direct influence on their lives, undermines efforts to pursue Community-Based Ecotourism. More profoundly, the study found that, as an analytical tool, social capital seems to provide a dynamic and holistic explanatory approach to the pursuance of Community-Based Ecotourism in land-claimed communities, compared with the dominant evaluative techniques in the tourism field. Another important practical implication is that social capital can be used to promote the analysis of communities as heterogeneous and evolving, as opposed to the assumptions of their homogeneity and static state. There is a strong possibility that social capital can also address power-relations, social exclusion and inequality, through consideration of both structural and cognitive indicators. The findings from this study make several contributions to the body of knowledge. Firstly, they provide a better understanding of social capital variables influencing community participation in conservation activities. This is of use when designing or developing future Collaborative Community-Based Natural Resources Management (CCBNRM) projects. Secondly, from a broader perspective, the study advises policy makers not to ignore related community policies which might impact community participation in CCBNRMs. This is essential in considering the direction of future conservation and rural development policy. Thirdly, they provide a framework for empowering local people and their communities to enhance participation in CCBNRM. In view of this, a binding conclusion can be made that social capital can be a vehicle through which the accumulation of different forms of capital can be achieved and contribute towards sustainable environmental management.
Thesis Submitted in fulfilment of the requirements for the degree of Doctor of Philosophy Geography and Environmental Studies University of Witwatersrand, Johannesburg School of Geography, Archaeology and Environmental Studies January 2017.
Keywords: Land reform beneficiaries--South Africa--KwaZulu Natal; Land reform--Developing countries; Land reform--Economic aspects--South Africa--KwaZulu Natal; Natural resources